MEMBACA MAKNA TRADISIONALITAS PADA ARSITEKTUR RUMAH TRADISIONAL - Tarigan, Riandy (Jurnal Arsitektur Komposisi, 2019)
Abstract: Traditional architecture built by the community is based on the view of cosmology and cultural symbolism that is owned by the community. This view is manifested into signs and meanings contained in space and architectural forms. Each of these spaces and forms is interpreted and trusted by the community to be the standard and always passed on to the next generation. Culture that occurs in society always changes and develops and can influence the meanings contained in the elements of the sign on the traditional house. The problem of this research is how to read the dynamics of meaning that occur due to the development of residents' needs to find out the dynamics of meaning that occurs in elements of traditional homes. The purpose of this study is to find out how the dynamics of the meaning are known and understood precisely through the signs contained in architectural elements. The object of the selected study is a Javanese traditional house which until now is still inhabited by some people who are on the north coast of Java in general and Kudus in particular. As a result, reading the dynamics of the meaning of traditional houses needs to be done with an interpretive approach to each element of elementary and complementary functions, as a whole, intact and interrelated (holistic).Keywords: Sign, dynamic meanning, traditional house, KudusAbstrak: Arsitektur tradisional dibangun oleh masyarakat dilandasi pandangan kosmologi dan simbolisme budaya yang dimiliki masyarakat. Pandangan tersebut diwujudkan menjadi tanda dan makna yang tertuang dalam ruang dan bentuk arsitektur. Setiap ruang dan bentuk dimaknai dan dipercayai oleh masyarakat menjadi hal yang baku dan diturunkan ke generasi berikutnya. Kebudayaan yang terjadi dalam masyarakat selalu berubah dan berkembang dan mempengaruhi makna-makna yang terdapat pada elemen-elemen tanda pada rumah tradisional. Masalah penelitian ini adalah bagaimana cara membaca dinamika makna yang terjadi akibat perkembangan kebutuhan penghuni untuk mengetahui dinamika makna yang terjadi pada elemen-elemen rumah tradisional. Tujuan penelitian adalah mengetahui bagaimana dinamika makna diketahui dan dipahami secara tepat melalui tanda-tanda yang terdapat pada elemen arsitektur. Objek studi adalah rumah tradisional Jawa yang sampai saat ini masih dihuni oleh sebagian masyarakat yang berada di pantai utara Jawa pada umumnya dan Kudus pada khususnya. Hasilnya, membaca dinamika makna rumah tradisional perlu dilakukan dengan pendekatan interpretatif pada setiap unsur fungsi elementer dan komplementer, secara menyeluruh, utuh dan saling terkait (holistik).Kata kunci : tanda, dinamika makna, rumah tradisional, Kudus.